Single enzyme nanoparticles armored by a thin silicate network: Single enzyme caged nanoparticles - Hong, Sung-Gil; Kim, Byoung Chan; Bin Na, Hyon; Lee, Jinwoo; Youn, Jongkyu; Chung, Seung-Wook; Lee, Chang-Won; Lee, Byoungsoo; Kim, Han Sol; Hsiao, Erik; Kim, Seong H.; Kim, Byung-Gee; et al. (ELSEVIER SCIENCE SA, 2017)
For the encapsulation of biomolecules in inorganic materials, we have developed a unique enzyme silicate conjugate material that consists of a self-assembled molecularly thin silicate layer on the surface of each individual enzyme molecule. The enzyme-silicate conjugate materials, called single enzyme caged nanoparticles (SECNs), were synthesized via the silica polymerization on the surface of enzyme molecule after solubilizing each enzyme molecule in hexane by using a tiny amount of surfactant, called "ion-pairing". SECNs possess near native enzyme activity in aqueous media with minimal substrate diffusional limitations, and are highly stable under the protection of silicate network cage. Due to their nearly molecular size, SECNs can also be adsorbed into mesoporous silica materials to yield robust and easily-recyclable enzymatic systems that can be used in a number of potential biocatalytic applications such as diagnostics, biosensors, biotransformations, biofuel production, bioremediation and CO2 capture. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ALPHA-CHYMOTRYPSIN; MESOPOROUS SILICA; MECHANISM; PROTEIN; IMMOBILIZATION